Perspektiven der Datenerhebungen im Straßengüterverkehr. Hintergrund und Motivation. - Babani, Jola; Liedtke, Gernot; Schröder, Stefan (Deutscher Verkehrs-Verl., 2010)
Das Leistungswachstum und die Strukturänderungen im Güterverkehr in den vergangenen Dekaden wurden vor allem durch die Globalisierung, die veränderte Güterstruktur und das Aufkommen neuer Produktionsformen forciert. Die Güterstrukturänderung von Massengütern zu hochwertigen Gütern sowie neue Produktionsformen wie Lean-Production haben zu neuen Anforderungen in der Transportlogistik geführt. Der Trend geht immer mehr zu kleinteiligen und hochfrequentierten Sendungen. Dadurch entsteht der Kundenwunsch, sämtliche Transportdienstleistungen "aus einer Hand" zu beziehen.

The statistics for heavy goods traffic by road - published by the Federal Office for Vehicles in conjunction with the Federal Office for Freight Traffic - offer politics and science essential information about Germany's freight transport by road. Recent developments in the fields of logistics, production and transport, which cause changes to the structure of freight transport by road, tend to place new demands on an empirical data base. It is only when data about such structural changes is recorded in an empirical way, and there is full understanding of decision-making in inter-connected transport networks, that forward looking logistics service providers can - with political support achieve any long term ecology- and economics- related improvements in freight transport systems.
Aspects of data collection concerning Germany's freight transport by road.
Keywords: Verkehr; Straßengüterverkehr; Verkehrspolitik; Mobilität; Verkehrsaufkommen; Verkehrsstatistik; Transport; Datenerhebung; Logistik; Transportleistung; Empirische Untersuchung